Adição do fator de crescimento semelhante à insulina-I ou melatonina ao meio de maturação de oócitos bovinos submetidos ao choque térmico - Ascari, Ivan Júnior (2015)
High ambient temperatures can cause reduced reproductive rates. In this context, IGF-I and melatonin can act as thermo-protector, reducing oxidative stress during the in vitro maturation (IVM) of bovine oocytes subjected to heat shock. The aims of this study were to evaluate the effects of IGF-I or melatonin added to the IVM medium of bovine oocytes, subjected to heat shock, on the quality and competence of oocyte development and the quality of the embryos. Follicles of three to eight millimeters in diameter were aspirated from ovaries collected at abattoirs of predominantly crossbred cows (Holstein-Gyr). We selected the cumulus-oocyte complexes that presented homogeneous cytoplasm with at least three layers of cells. Two experiments were performed, in which the addition of IGF-I (0, 25 e 100 ng/mL) or melatonin (0, 10-6 e 10-4 M) to the IVM medium, under two incubation conditions, were evaluated. The incubation conditions were conventional, with 24 hours at 38.5°C, or heat shock with 12 hours at 41ºC followed by 12 hours at 38.5°C. There was no interaction between incubation condition and IGF-I or melatonin in any analyze (P > 0.05). In Experiment I, the addition of IGF-I increased mitochondrial activity (P < 0.01) and the production of reactive oxygen species - ROS (P < 0.01), while reducing blastocyst rate in the seven and eight days (P < 0.01), as well as apoptotic cells rate of inner cell mass (P < 0.01). Heat shock increased the percentage of TUNEL-positive oocytes (P < 0.01) and the production of ROS (P < 0.01), and reduced mitochondrial activity (P < 0.01). In Experiment II, the addition of melatonin reduced the production of ROS (P < 0.01) in the oocytes, while heat shock increased (P < 0.01) its production. Mitochondrial activity was not affected (P > 0.05) by melatonin, but was reduced by heat shock. Heat shock also reduced the percentage of oocytes that have progressed to metaphase II stage (P < 0.01) and blastocyst rate in seven (P = 0.02) and eight (P < 0.01) days. In conclusion, the supplementation of IGF-I or melatonin to IVM medium improves the quality of the embryos produced. One of the most important results of IGF-I was the increased mitochondrial activity, whereas, for melatonin, it was the reduction of oxidative stress in the oocyte.